The Influence of Emotional Intelligence, Learning Facilities, Parental Attention, and Peers on the Academic Achievement of SMAN 16 Padang Students Thru Learning Discipline as an Intervening Variable - Yasmin Zahra; Jolianis; Fifi Yasmi (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the influence of Emotional Intelligence, Learning Facilities, Parental Attention, and Peer Groups on Students’ Academic Achievement at SMA Negeri 16 Padang, with Learning Discipline as an intervening variable in the subject of Economics. The research employs a quantitative approach with an associative design. The population consists of 440 students from classes XE1–XE11 in the 2024/2025 academic year, with a sample of 209 students selected using Random Proportional Sampling. The research instrument is a closed-ended questionnaire, and the data were analyzed using path analysis with hypothesis testing conducted through the t-test. The findings reveal that: (1) Emotional intelligence, learning facilities, parental attention, and peer groups do not have a significant effect on learning discipline, but each indirectly affects academic achievement through learning discipline; (2) Emotional intelligence, learning facilities, parental attention, peer groups, and learning discipline have a significant direct effect on academic achievement.